2013
DOI: 10.1111/ijfs.12121
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of chelating factors, trace minerals and their estimated bioavailability in Italian and African sorghum (Sorghum bicolor (L.) Moench) porridges

Abstract: Factors able to modulate chelating factors, trace minerals and their bioavailability were investigated in porridges of five sorghum (Sorghum bicolor (L.) Moench) varieties: from Nigeria, Senegal, Burkina Faso and two from Italy. Effects of variety and traditional fermentation and cooking were assessed on ironbinding phenolic groups, phytates and iron and zinc content and bioavailability. Chelating factors, trace elements as well as the effect of processing (mainly fermentation) were modulated by variety. Ferme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 31 publications
0
24
1
Order By: Relevance
“…The reduction of PA in African fermented foods is highly varied with some finding no degradation (150,151) , less than 50% degradation (15,113,152,153) and others finding more than 50% degradation (15,112,113,(154)(155)(156) . Several factors seem to influence the reduction of mineral binders in these type of fermented foods.…”
Section: Reduction Of Iron and Zinc Binders In Naturally Fermented Afmentioning
confidence: 99%
See 2 more Smart Citations
“…The reduction of PA in African fermented foods is highly varied with some finding no degradation (150,151) , less than 50% degradation (15,113,152,153) and others finding more than 50% degradation (15,112,113,(154)(155)(156) . Several factors seem to influence the reduction of mineral binders in these type of fermented foods.…”
Section: Reduction Of Iron and Zinc Binders In Naturally Fermented Afmentioning
confidence: 99%
“…(155) These differences clearly highlight that some matrices favor the reduction of PA than others. Proietti, et al (156) found PA degradation between 58 -72% of several fermented porridges produced from different sorghum varieties. The endogenous phytase activity of the sorghum flours varied between 0.17 -0.21 PU/g and increasing to 0.64 -3.44 PU/g in the fermented slurries and this demonstrates that PA reduction is also variety dependent.…”
Section: Reduction Of Iron and Zinc Binders In Naturally Fermented Afmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional sorghum processing such as fermentation or cooking may modulate the presence of chelating factors, hence nutrient bioavailability (Towo et al ., ; Abdelhaleem et al ., ). In a previous paper, we showed that chelating factors, trace elements as well as the effect of processing (mainly fermentation), were modulated by variety (Proietti et al ., ). In fermented samples, iron‐binding phenolic groups and phytate content decreased to a maximum of 49% and 72%, respectively; conversely, phytase activity increased 3.4–16.4 fold, leading to enhancement of iron and zinc estimated bioavailability.…”
Section: Introductionmentioning
confidence: 97%
“…The in vitro results were integrated by the iron bioavailability estimated through the use of the algorithm of Hallberg and Hultén (), as indicator of the modulation of sorghum nutritional value. The results are discussed in comparison with previous findings from analytical assays and molar ratios, which showed significant differences related to both variety and treatment (Proietti et al ., ).…”
Section: Introductionmentioning
confidence: 97%